The Notch inhibitor, FLI-06, increases the chemosensitivity of head and neck Squamous cell carcinoma cells to taxanes-based treatment - Czerwonka, Arkadiusz; Kałafut, Joanna; Wang, Shaoxia; Anameric, Alinda; Przybyszewska-Podstawka, Alicja; Toriseva, Mervi; Nees, Matthias (Elsevier, 2025)
Aberration of Notch signaling is one of the key events involved in the development and progression of head and neck squamous cell carcinoma (HNSCC). The Notch pathway controls the tissue-specific differentiation of normal squamous epithelial cells and is frequently altered in squamous carcinomas, thus affecting their proliferation, growth, survival, and chemosensitivity or resistance against anti-cancer agents. In this study, we show that the use of novel, small-molecule inhibitors of Notch signaling, such as FLI-06, can have a beneficial effect on increasing the chemosensitivity of HNSCC to taxane-based chemotherapy. Inhibition of Notch signaling by FLI-06 alone virtually blocks the proliferation and growth of HNSCC cells in both 2D and 3D cultures and the zebrafish model, which is accompanied by down-regulation of key Notch target genes and proteins. Mechanistically, FLI-06 treatment causes cell cycle arrest in the G1-phase and induction of apoptosis in HNSCC, which is accompanied by increased c-JunS63 phosphorylation. Combining FLI-06 with Docetaxel shows a synergistic effect and partially blocks the cell growth of aggressive HNSCC cells via enhanced apoptosis and modification of c-JunS243 phosphorylation via GSK-3β inhibition. In conclusion, inhibition of Notch signaling in HNSCC cells that retain active Notch signaling significantly supports taxane-based anticancer activities via modulation of both the GSK-3β and the c-Jun.